Pleural, abdominal, and pericardial lymphocytic effusion - Veronika Kloboves Prevodnik; Živa Ledinek; Aleš Rode; Gorana Gašljević (Onkologija)
Lymphocytic effusion is a complication of several diseases. The main causes of most lymphocytic effusions are malignomas and tuberculosis. Lymphocytes in effusion can be reactive or neoplastic. Reactive lymphocytic effusion develops due to inflammation, systemic and autoimmune diseases, carcinosis, and other rare causes. Malignant lymphocytic effusions are mostly found in patients during the progression of nodal and extranodal lymphomas to the pleural, pericardial or abdominal cavity while effusions caused by lymphomas evolving from serous surfaces are very rare. Cytopathological diagnostic of lymphomas in effusions is based on clinical, morphological, immunophenotypic and molecular features of the disease. According to the international guideless we categorize lymphoproliferative diseases in effusions in five categories: nondiagnostic, benign, atypical cells of undetermined significance, suspicious for malignancy and malignant.